PENDAYAGUNAAN NAFKAH PRODUKTIF PADA ANAK: (Studi Kasus Desa Sumber Jeruk Kabupaten Bondowoso) - Fatmawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
The fulfilling a living importance for children, especially educationproviding can be seen in terms of the axiology of legal benefits where providing forchildren is a medium for achieving social welfare, by fulfilling children'smaintenance, it means the same as preparing future human resources who havequality, because in There are three aspects of fulfilling children's basic needs,namely primary needs, children's spiritual (psychological) needs and intellectualneeds. Good fulfillment of these needs can be a form of utilizing productive incometo improve the quality of human resources in the future. Sumber Jeruk Village as oneof the villages at the end of Bondowoso district is a village that has a fairly goodlevel of concern for the world of education, even though it is at the very edge but theenthusiasm for community education is very good, this is evident from the author'sfindings on several institutions that have existed since the beginning in 2000, morethan that there were various graduates from various senior secondary educationinstitutions who participated in coloring the community both in terms of theeconomy and so on. This study aims to determine the forms of child support,especially in the field of education and their impact on the village. In this paper themethodology used is qualitative through a phenomenological approach, which is anapproach used by a group of researchers to interpret a phenomenology that occursin a particular group or community, in this case the people in Sumber Jeruk village,Bondowoso district. The findings in this study include that the people in SumberJeruk village carry out quite good educational planning by taking into account thepotential of the children and the economic capacity of the family, this allows eachfamily to fulfill their education needs more objectively not by following trends and soon. The results obtained from these efforts are the creation of a scientific range thatis owned by youth in the village, the variety of education pursued so that the villagedoes not lack human resources, ranging from teachers, modern farmers, to businesspeople.